IN VIVO EVALUATION OF ANTI-THALASSAEMIC ACTIVITY OF TERMINALIA CATAPPA CRUDE EXTRACTS IN SWISS ALBINO MICE - Priyanka C, Jyothi B, (Chelonian Research Foundation, 2024)
Iron overload disorders, such as thalassemia, pose significant health challenges worldwide. In this study, we evaluated the efficacy of Terminalia catappa ethyl acetate crude extract (TCEACE) in reducing serum Fe³⁺ levels. Leaves of Terminalia catappa were collected, dried, and sequentially extracted using chloroform, acetone, and ethyl acetate. In this animal study, male Swiss Albino mice were used to evaluate the effects of T. catappa ethyl acetate crude extract (TCEACE) on iron overload. The mice received intraperitoneal injections of iron dextran to induce iron overload, mimicking thalassemia-related chronic iron accumulation. TCEACE was administered at different dosages, and serum iron levels were assessed. Our results demonstrate that TCEACE significantly outperforms the standard drug (DFO) and effectively mitigates iron overload. Both group-5 (50 mg/kg TCEACE) and group-6 (100 mg/kg TCEACE) exhibited marked reductions in serum iron levels, emphasizing a dose-dependent response. These findings highlight TCEACE as a promising natural alternative for managing iron-related conditions, warranting further investigation for clinical applications in patients with iron overload disorders.